A procedural framework for robust environmental management of deep-sea mining projects using a conceptual model. (October 2017) - Durden, Jennifer M.; Murphy, Kevin; Jaeckel, Aline; Van Dover, Cindy L.; Christiansen, Sabine; Gjerde, Kristina; Ortega, Aleyda; Jones, Daniel O.B.
Abstract: Robust environmental management of deep-sea mining projects must be integrated into the planning and execution of mining operations, and developed concurrently. It should follow a framework indicating the environmental management-related activities necessary at each project phase, and their interrelationships. An environmental management framework with this purpose is presented in this paper; it facilitates the development of environmental information and decision-making throughout the phases of a mining project. It is based environmental management frameworks used in allied industries, but adjusted for unique characteristics of deep-sea mining. It defines the gathering and synthesis of information and its use in decision-making, and employs a conceptual model as a growing repository of claim-specific information. The environmental management activities at each phase have been designed to enable the implementation of the precautionary approach in decision making, while facilitating review of adaptive management measures to improve environmental management as the quantity and quality of data increases and technologies are honed. This framework will ensure fairness and uniformity in the application of environmental standards, assist the regulator in its requirements to protect the environment, and benefit contractors and financiers by reducing uncertainty in the process. Highlights: Environmental management must be integral to the planning and execution of projects. A framework for environmental management of deep-sea mining projects is presented. A conceptual model of the project is iteratively updated to store all information. It facilitates application of the precautionary approach and mitigation hierarchy. It includes appropriate review for project adaptation.